Dekonstruksi Marwah Mahkamah Konstitusi Terkait Krisis Legitimasi Tafsir Etika Konstitusional - Edward Benedictus Roring (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
The democratic journey of the Indonesian nation has always experienced quite brilliant ups and downs and is not in accordance with the norms of good civility. By disobeying various things that always prioritize various principles of democracy and social life for society. The Constitutional Court (MK) as an institution that safeguards the constitution and protects the supremacy of law in Indonesia plays an important role in ensuring the sustainability of democratic principles and the protection of human rights. However, in recent years, the dignity of the Constitutional Court has often been questioned due to various controversies surrounding the integrity, independence and legitimacy of this institution. This article aims to analyze the causes and impacts of the collapse of the MK's dignity on legal governance and democratic stability in Indonesia. Using a normative-empirical approach, this article discusses the challenges faced by the Constitutional Court, including political interference, external pressure, and internal problems related to the code of ethics and professionalism of judges. This study found that the legitimacy crisis experienced by the Constitutional Court not only damaged the credibility of the institution but also threatened the stability of the law and constitutional order in Indonesia.